Interactions between Scenedesmus and Microcystis may be used to clarify the role of secondary metabolites. Issue 1 (24th July 2012) - Harel, Moshe; Weiss, Gad; Lieman‐Hurwitz, Judy; Gun, Jenny; Lev, Ovadia; Lebendiker, Mario; Temper, Violeta; Block, Colin; Sukenik, Assaf; Zohary, Tamar; Braun, Sergei; Carmeli, Shmuel; et al.
Summary Microcystis sp. are major players in the global intensification of toxic cyanobacterial blooms endangering the water quality of freshwater bodies. A novel green alga identified as Scenedesmus sp., designated strain huji (hereafter S. huji), was isolated from water samples containing toxic Microcystis sp. withdrawn from Lake Kinneret (Sea of Galilee), Israel, suggesting that it produces secondary metabolites that help it withstand the Microcystis toxins. Competition experiments suggested complex interaction between these two organisms and use of spent cell‐free media from S. huji caused severe cell lysis in various Microcystis strains. We have isolated active metabolites from the spent S. huji medium. Application of the concentrated allelochemicals interfered with the functionality and perhaps the integrity of the Microcystis cell membrane, as indicated by the rapid effect on the photosynthetic variable fluorescence and leakage of phycobilins and ions. Although some activity was observed towards various bacteria, it did not alter growth of eukaryotic organisms such as the green alga Chlamydomonas reinhardtii.